1975
DOI: 10.2307/2258604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moisture Stress on the Growth and Reproduction of Three Annual Species from an Arid Region of Western Australia

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.British Ecological Society, Wiley are collaborating with JSTOR to digitize, preserve and extend access to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
(8 reference statements)
2
7
0
Order By: Relevance
“…But only under limited water supply did onset of reproduction have a direct and total negative selection effect on fitness, favouring early onset of reproduction. Earlier we reported (Volis et al, 2002b) that water stress significantly delayed onset of reproduction, a pattern found for other annuals from arid environments (Mott & McComb, 1975;Fox, 1990;van Rooyen et al, 1991;Steyn et al, 1996). The results of our selection analysis suggest that, although water stress causes a delay of reproduction in comparison with an optimal environment because of physiological constraints that limited water supply imposes on plant development, plants that initiate reproduction earlier are favoured.…”
Section: Discussionsupporting
confidence: 67%
“…But only under limited water supply did onset of reproduction have a direct and total negative selection effect on fitness, favouring early onset of reproduction. Earlier we reported (Volis et al, 2002b) that water stress significantly delayed onset of reproduction, a pattern found for other annuals from arid environments (Mott & McComb, 1975;Fox, 1990;van Rooyen et al, 1991;Steyn et al, 1996). The results of our selection analysis suggest that, although water stress causes a delay of reproduction in comparison with an optimal environment because of physiological constraints that limited water supply imposes on plant development, plants that initiate reproduction earlier are favoured.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast to the widely held view that the onset of reproduction in desert, and sometimes in mesic, annuals is stimulated by drought (Went, 1948(Went, , 1949Rathcke & Lacey, 1985;Lacey, 1986), our results suggest the opposite. Water stress significantly delayed onset of reproduction, a pattern found for other annuals from arid environments (Mott & McComb, 1975;Fox, 1990;van Rooyen et al, 1991;Steyn et al, 1996). There was no difference in delaying response among plants of different origin, suggesting a similar mechanism for switch from vegetative to reproductive stage and similar phenotypic plasticity for this transition for the four ecotypes.…”
Section: Discussionmentioning
confidence: 51%
“…Etherington (1967) found that even very slight water deficits reduced photosynthesis in Alopecurus pratensis considerably. That the adverse effect of water stress on growth is variable for different species and depends on their relative drought tolerance has been shown by various authors (Mott andMcComb 1975, Gerakis et al 1975). The relative decrease in shoot and root dry weights was different in different species.…”
Section: Resultsmentioning
confidence: 87%
“…Lolium showed the least reduction in total biomass. Several authors have reported a reduction in the dry matter yield of grasses caused by water stress (Mott andMcComb 1975, Gerakis et al 1975). This decrease is evidently due to a decline in net Kozlowski (1964Kozlowski ( , 1968), Slatyer (1967), Crafts (1968), and Kramer (1969) have also reported that a decrease in turgor due to water stress influences cell expansion, which in turn causes reduction in photosynthesis.…”
Section: Resultsmentioning
confidence: 99%